Comparison of thermal insulation capability between conventional and nanostructured plasma sprayed YSZ coating on Ni3Al substrates. Issue 5 (1st April 2017) - Chen, Dan; Luo, Fa; Lou, Xufei; Qing, Yuchang; Zhou, Wancheng; Zhu, Dongmei
Abstract: Conventional and nanostructured yttria-stabilized zirconia(YSZ) as thermal barrier coatings were directly deposited on Ni3 Al intermetallic compound substrates without bond coating by atmospheric plasma spraying. The adherence, thermal insulation capability, microstructure, porosity and sintering resistance of these two kinds of coatings were studied. For the thickness of 150 µm YSZ coating without bond coating, the temperature drop ( ∆ T=98 ℃) of the nanostructured YSZ coating at 1200 ℃ increases by 50.8% compared with that of the conventional YSZ coating ( ∆ T=65 ℃). It is shown that the nanostructured YSZ coating has higher thermal insulation capability than the conventional YSZ coating, which is mainly due to its special microstructure with more semi-molten particles (21.78±0.54%), higher porosity (8.81±0.35%) and better sintering resistance.